HYDAMTIQ, a selective PARP‐1 inhibitor, improves bleomycin‐induced lung fibrosis by dampening the TGF‐β/SMAD signalling pathway. Issue 2 (4th October 2016) - Lucarini, Laura; Durante, Mariaconcetta; Lanzi, Cecilia; Pini, Alessandro; Boccalini, Giulia; Calosi, Laura; Moroni, Flavio; Masini, Emanuela; Mannaioni, Guido
Abstract: Idiopathic pulmonary fibrosis is a severe disease characterized by excessive myofibroblast proliferation, extracellular matrix and fibrils deposition, remodelling of lung parenchyma and pulmonary insufficiency. Drugs able to reduce disease progression are available, but therapeutic results are unsatisfactory; new and safe treatments are urgently needed. Poly(ADP‐ribose) polymerases‐1 (PARP‐1) is an abundant nuclear enzyme involved in key biological processes: DNA repair, gene expression control, and cell survival or death. In liver and heart, PARP‐1 activity facilitates oxidative damage, collagen deposition and fibrosis development. In this study, we investigated the effects of HYDAMTIQ, a potent PARP‐1 inhibitor, in a murine model of lung fibrosis. We evaluated the role of PARP on transforming growth factor‐β (TGF‐β) expression and TGF‐β/SMAD signalling pathway in lungs. Mice were intratracheally injected with bleomycin and then treated with either vehicle or different doses of HYDAMTIQ for 21 days. Airway resistance to inflation and lung static compliance, markers of lung stiffness, were assayed. Histochemical and biochemical parameters to evaluate TGF‐β/SMAD signalling pathway with alpha‐smooth muscle actin (αSMA) deposition and the levels of a number of inflammatory markers (tumour necrosis factor‐α, interleukin‐1β, iNOS and COX‐2) were performed. Bleomycin administration increased lung stiffness. It also increased lung PARP activity, TGF‐β levels, pSMAD3 expression, αSMA deposition and content of inflammatory markers. HYDAMTIQ attenuated all the above‐mentioned physiological, biochemical and histopathological markers. Our findings support the proposal that PARP inhibitors could have a therapeutic potential in reducing the progression of signs and symptoms of the disease by decreasing TGF‐β expression and the TGF‐β/SMAD transduction pathway.